Semi-automated buildup and calibration of conceptual sewer models. (July 2017) - Kroll, S.; Wambecq, T.; Weemaes, M.; Van Impe, J.; Willems, P.
Abstract: Building conceptual sewer models can be a time-consuming task, especially for large or complex models or models that require input data that might be difficult/tedious to obtain manually. This paper presents a semi-automated procedure for the buildup and calibration of one conceptual model that requires detailed input data such as throttle dimensions, pump curves or water level-storage relations. The procedure uses a hydrodynamic model as basis for sewer network data to create the model layout. A standardised series of composite rainfall events is applied to the hydrodynamic model in order to obtain the necessary reference data for the automated calibration of the conceptual model. Both model buildup and calibration are illustrated by means of a case study. Comparison of results of the hydrodynamic and conceptual model for a 1 year long-term series shows that the automated buildup and calibration can lead to an accurate conceptual model in short time. Highlights: An automated buildup and calibration routine for conceptual sewer models is proposed. Hydrodynamic models are used as a basis for the model buildup. The routine can handle complex data such as required for modelling of backwater at throttle structures. The automatically built and calibrated model delivers highly accurate results.